How do you multiply #(m - 5)(m + 2)#?

1 Answer
Jun 15, 2016

Answer:

You multiply element by element.

Explanation:

When you multiply two parenthesis you have to multiply each element inside the first parenthesis for each element of the second parenthesis.

#(m-5)(m+2)#

#=m*m+m*2+(-5)*m+(-5)*2#

#=m^2+2m-5m-10#

Now the terms with the same power can be summed together.
In this case the only terms with the same power are #2m# and #-5m# and their sum is #2m-5m=-3m#. The final result is

#=m^2+2m-5m-10#

#=m^2-3m-10#.